2020
DOI: 10.1109/tthz.2020.3004517
|View full text |Cite
|
Sign up to set email alerts
|

Importance and Requirement of Frequency Band Specific RF Probes EM Models in Sub-THz and THz Measurements up to 500 GHz

Abstract: In this paper, we present on-silicon structures onwafer measurements up to 500 GHz and a comprehensive electromagnetic (EM) simulation analysis to understand nonideal behaviour in the measured data. The EM simulations are performed in such a way that the simulation setup remains very close to the physical measurement environment where a faithful true EM model of the RF probes is an essential requirement. In this process, four different RF probes used during measurements in the frequency bands 1 GHz-110 GHz, 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…In the 140-220 GHz band, though, both the measurement and the simulation with probes diverge from the trend indicated by the intrinsic simulation, particularly the port-to-port capacitance (C 12 ), which becomes clearly nonphysical. This fact may be traced back to the port-1 to port-2 crosstalk between the two RF probes due to their design [28]. It has been showed that a coplanar probe with a much simpler design does not present this behavior in this band [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 140-220 GHz band, though, both the measurement and the simulation with probes diverge from the trend indicated by the intrinsic simulation, particularly the port-to-port capacitance (C 12 ), which becomes clearly nonphysical. This fact may be traced back to the port-1 to port-2 crosstalk between the two RF probes due to their design [28]. It has been showed that a coplanar probe with a much simpler design does not present this behavior in this band [24].…”
Section: Resultsmentioning
confidence: 99%
“…After creation of the 3D models of each structure, simulation is carried out much like described in [24]. Thanks to the optical microscope imaging, several G-S-G probe models replicating the GGB® Picoprobe RF probes with a 50/100 µm pitch for each band up to 500 GHz have been designed in HFSS [25].…”
Section: Em Simulation Proceduresmentioning
confidence: 99%
“…In contrast, the calibration in WR3.4 and 2.2 band gives more realistic results. As shown in [19], this is attributed to highly downscaled probes restraining and guiding the EM field towards the structure in a confined way. In a second step, the EM-SPICE co-simulation is carried out.…”
Section: A Analysismentioning
confidence: 95%
“…3. It is an optimized version of the test structures compared to [19]: it is dedicated to on-wafer TRL calibration with a large space between structures and it uses staggered test structures to reduce the influence of adjacent structures. Also, the pad geometry has been optimized to be compatible with 100 and 50 µm pitch for millimeter-wave and sub-millimeter-wave measurements.…”
Section: A Test Structuresmentioning
confidence: 99%
“…In the same way, this effect can be completely suppressed by changing the probe geometry used below 220 GHz by using the front-end geometry of the WR3.4 or WR2.2 probe. Therefore, the two calibration kits developed in [10], [18] and the one from this paper are obviously incompatible with the 220 GHz Picoprobe from GGB probe, and the calibration kits deserve to be redesigned taking into account the geometry of this probe. Another solution would be to use better designed probes.…”
Section: Models Of Probes In the Whole Frequency Bandmentioning
confidence: 99%